2013
DOI: 10.1016/j.ab.2013.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary validation of a plate-based CB1/CB2 receptor functional assay

Abstract: Cannabinoids receptors (CB) are being targeted therapeutically for the treatment of anxiety, obesity, movement disorders, glaucoma, and pain. More recently, cannabinoid agonists have displayed anti-proliferative activity against breast cancer and prostate cancer in animal models. In order to study cannabinoid receptor ligands, we have developed a novel plate-based assay that measures internalization of CB1/CB2 receptors by determining the change in the intracellular levels of the radiolabeled agonists: [3H]-Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…As demonstrated by the increased GFAP staining, astrocytes remained activated after pre-treatment with AM251 (Figure 2 B-D), suggesting that the endocannabinoid system is involved in MCS-induced analgesia by inhibiting astrocyte activity. Given that (1) MCS inhibits astrocyte and microglial activation; (2) the CB2 receptor, rather than CB1, is directly involved in astrocyte and microglial inhibition in neuropathic pain conditions [ 47 - 49 ]; and (3) AM251 can act as a CB2 inverse agonist [ 50 , 51 ], we next evaluated the CB2 labeling pattern in the spinal cord of MCS-responsive and MCS-refractory animals.
Figure 2 Participation of the cannabinoid system in motor cortex stimulation (MCS)-induced analgesia.
…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated by the increased GFAP staining, astrocytes remained activated after pre-treatment with AM251 (Figure 2 B-D), suggesting that the endocannabinoid system is involved in MCS-induced analgesia by inhibiting astrocyte activity. Given that (1) MCS inhibits astrocyte and microglial activation; (2) the CB2 receptor, rather than CB1, is directly involved in astrocyte and microglial inhibition in neuropathic pain conditions [ 47 - 49 ]; and (3) AM251 can act as a CB2 inverse agonist [ 50 , 51 ], we next evaluated the CB2 labeling pattern in the spinal cord of MCS-responsive and MCS-refractory animals.
Figure 2 Participation of the cannabinoid system in motor cortex stimulation (MCS)-induced analgesia.
…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported a plate-based assay that measures internalization of radiolabeled agonists for CB1 and CB2 receptors in intact CHO cells (Dossou et al 2013 ). Consistent with our hypothesis, MNF was found to selectively block internalization of the CB1 receptor agonist, Win55-212-2, with an IC 50 of 101 nmol/L (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were routinely maintained in DMEM supplemented with l -glutamine, 1% penicillin/streptomycin solution, and 10% FBS. CHO cells stably expressing CB1 receptors or CB2 receptors (Dossou et al 2013 ) were maintained in DMEM:F12 (1:1) supplemented with l -glutamine, 2.44 g/L sodium bicarbonate, penicillin/streptomycin, and 10% FBS. All cell lines were cultured in a humidified CO 2 incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work has demonstrated that first-generation CB1 receptor blockers, such as AM251 and rimonabant, stimulated β-cell proliferation both in vitro and in vivo 11 26 . Recently, a novel CB1 receptor inverse agonist with low brain penetrance named JD-5037 has been characterized 27 28 29 . This compound was shown to protect β-cell function by reducing islet inflammation and to restore glycemic plasma levels to normal in ZDF rats 30 .…”
mentioning
confidence: 99%